2019
DOI: 10.31631/2073-3046-2019-18-4-101-119
|View full text |Cite
|
Sign up to set email alerts
|

Review of Grippol Family Vaccine Studies and Modern Adjuvant Development

Abstract: 1 ФГАОУ ВО Первый МГМУ им. И. М. Сеченова Минздрава России (Сеченовский Университет) Минздрава России, Москва 2 НПО Петровакс Фарм, Москва Обзор исследований вакцин семейства Гриппол и развития современных адъювантов Резюме Актуальность. Вакцинация остается основой профилактики наиболее значимых инфекционных заболеваний, включая грипп. На сегодняшний день разработано и применяется большое число вакцин, в том числе с применением различных адьювантов. Цель работы. Углубиться в историю поиска эффективных адъювант… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(28 reference statements)
0
3
0
2
Order By: Relevance
“…Our study also obtained data on the activation of TLR3 expressed on granulocytes and lymphocytes after repeated administration of one dose of adjuvanted influenza vaccine (as is recommended according to present guidelines-annually) and on monocytes upon administration of two doses simultaneously and, conversely, the absence of TLR3 activation upon the first vaccination with one dose. Consequently, annual vaccination against influenza using the same adjuvanted vaccine contributes to temporary nonspecific prevention of respiratory infections [57][58][59][60][61][62][63]. Simultaneous administration of two doses of vaccines also contributes to TLR3 expression which is observed only on monocytes, and, probably, the protective effect against other respiratory infections may be less pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also obtained data on the activation of TLR3 expressed on granulocytes and lymphocytes after repeated administration of one dose of adjuvanted influenza vaccine (as is recommended according to present guidelines-annually) and on monocytes upon administration of two doses simultaneously and, conversely, the absence of TLR3 activation upon the first vaccination with one dose. Consequently, annual vaccination against influenza using the same adjuvanted vaccine contributes to temporary nonspecific prevention of respiratory infections [57][58][59][60][61][62][63]. Simultaneous administration of two doses of vaccines also contributes to TLR3 expression which is observed only on monocytes, and, probably, the protective effect against other respiratory infections may be less pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…On a number of model compounds, it was shown that the immunogenicity and protective properties of antigens attached to the Azoximer bromide carrier increase 10-fold with an increase in both the antibody and cell-mediated immune response, the synthesis of all classes of protective antibodies (IgM, IgG, IgA) is enhanced, but the synthesis of allergic IgE antibodies is not stimulated. Thus, some synthetic polyions are strong adjuvants and polyclonal activators of B-and T-lymphocytes ( 41 ). Grippol® plus is produced according to international GMP and ISO ISO:9001 standards in clean rooms on the filling line with hurdle technology, which allows excluding the mercury-containing preservative (thiomersal) from the composition of vaccine.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Grippol® Plus assisted by polymer-based vaccine delivery systems, is in Phase III clinical trial to treat influenza infections [205] . For peptide/protein-based vaccine delivery systems, EBV gp350-Ferritin vaccine developed by NIAID is in Phase I clinical trial for the treatment of Epstein-Barr Virus Infections.…”
Section: Clinical Vaccine Delivery Systemsmentioning
confidence: 99%